Stakeholder relationship management in food exports - Pulkkinen, Kira (My University, 2025)
Geopolitical changes occurring globally are reflected in international business, creating uncertainty for companies operating in global markets. This study examines the role of stakeholder relationships and customer relationship in the context of food exports and the geopolitical business environment. The aim of the study is to explore how food export companies can manage their stakeholder relationships in an unstable global environment. The study places particular emphasis on customer relationships, which are identified in the literature as one of the most important stakeholder groups for companies. The study combines theoretically two widely recognized management theories. Stakeholder relationship management theory highlights the importance of identifying key stakeholders, while customer relationship management theory focuses on strategies and practices for fostering strong, long-term relationships with customers. By integrating both management approaches, this study offers a comprehensive insight of managing key relationships within the context of geopolitical risk management. The empirical part of the study relies on a qualitative approach, with data collected through semi-structured interviews. The data consists of interviews with three export experts, whose insights have been utilized to build a deeper understanding of the research phenomenon. The experts selected for the interviews represent Finnish food export companies and have several years of experience in the food industry, including managing various stakeholders. The findings from the thematic analysis have been reflected against previous literature and the theoretical framework. The findings of the study demonstrate that trust-based, long-term stakeholder relationships play an essential role in the risk management of international companies during times of geopolitical uncertainty and tension. Furthermore, the study emphasizes the importance of continuous monitoring of external factors and the ability to respond for companies aiming to maintain their competitiveness and ensure business continuity in international markets. However, mere reaction is not enough, as the research confirms that identifying the long-term effects of geopolitical risks is challenging. This adds a need for a deeper understanding of geopolitical factors and a context-specific and proactive approach to manage key relationships. This research provides valuable insights for food export companies as well as other organizations operating in international business, deepening the understanding of the role of external factors in stakeholder relationship management in an international context.

Maailmalla tapahtuvat geopoliittiset muutokset heijastuvat kansainväliseen liiketoimintaan ja luovat epävarmuutta yrityksille, jotka toimivat kansainvälisillä markkinoilla. Tämä tutkimus tarkastelee sidosryhmäsuhteiden ja asiakassuhteiden roolia elintarvikeviennin ja geopoliittisen toimintaympäristön yhteydessä. Tutkimuksen tarkoituksena on selvittää, miten elintarvikealan vientiyritykset voivat hallita keskeisimpiä sidosryhmäsuhteitaan epävakaassa kansainvälisessä ympäristössä. Erityinen painopiste on asiakassuhteissa, jotka kirjallisuuden mukaan muodostavat yhden yritysten tärkeimmistä sidosryhmistä. Tutkimus yhdistää kaksi laajalti tunnistettua johtamisteoriaa. Sidosryhmäsuhteiden hallinnan teoria korostaa avainsidosryhmäsuhteiden tärkeyttä, kun asiakassuhteiden hallinnan teoria keskittyy puolestaan strategioihin ja käytäntöihin, joilla pyritään rakentamaan ja ylläpitämään vahvoja, pitkäaikaisia asiakassuhteita. Yhdistämällä molemmat johtamislähestymistavat, tutkimus tarjoaa kattavan käsityksen avainsidosryhmäsuhteiden hallinnasta geopoliittisten riskienhallinnan yhteydessä. Tutkimuksen empiirinen osuus pohjautuu kvalitatiiviseen lähestymistapaan, jossa aineisto on kerätty puolistrukturoiduilla haastatteluilla. Aineisto koostuu kolmen elintarvikeviennin asiantuntijan haastatteluista, joiden näkemyksistä on pyritty rakentamaan syvällinen ymmärrys tutkimusilmiöstä. Haastatteluihin valitut asiantuntijat edustavat suomalaisia, kansainvälisellä kentällä toimivia, elintarvikevientiyrityksiä ja heillä on usean vuoden kokemus elintarvikealalta, mukaan lukien eri sidosryhmien hallinta. Temaattisen analyysin havainnot on peilattu aiempaan kirjallisuuteen ja teoreettiseen viitekehykseen. Tutkimuksen löydökset osoittavat, että luottamukseen perustuvat pitkäaikaiset sidosryhmäsuhteet toimivat keskeisenä osana kansainvälisten yritysten riskienhallintaa geopoliittisen epävarmuuden ja jännitteiden aikana. Lisäksi tutkimus korostaa ulkoisten tekijöiden jatkuvaa seurantaa ja reagointikyvyn merkitystä yrityksille, jotka pyrkivät säilyttämään kilpailukykynsä ja varmistamaan liiketoimintansa jatkuvuuden kansainvälisillä markkinoilla. Pelkkä reagointi ei kuitenkaan riitä, sillä tutkimus vahvistaa, että geopoliittisten riskien pitkäaikaisten vaikutusten tunnistaminen on haastavaa. Tämä lisää tarvetta syvällisemmälle ymmärrykselle geopoliittisista tekijöistä sekä kontekstisidonnaista ja ennakoivaa lähestymistapaa keskeisten suhteiden hallintaan. Tutkimus tarjoaa arvokasta tietoa elintarvikeviennin yrityksille sekä muille kansainvälisessä liiketoiminnassa toimiville organisaatioille, syventäen ymmärrystä ulkoisten tekijöiden roolista sidosryhmäsuhteiden hallinnassa kansainvälisessä ympäristössä.
Keywords: geopolitics, stakeholder management, customer relationship management, risk management, food industry, geopolitiikka, sidosryhmäjohtaminen, asiakkuushallinta, riskien hallinta, elintarvikevienti